The political economy of migrant smuggling: The case of conflict in Mali - Hinkel, Thomas (AUC Knowledge Fountain, 2018)
The extensive human smuggling networks that have emerged around North Africa and the Sahel have inaugurated a significant shift in the economic landscape of a region that has traditionally been characterized by the gray economy and precarious political arrangements. Ample and detailed research has been produced that highlights how militia groups and non-state actors have been tapping into these flows (via taxation of routes and racketeering against non-armed smuggling enterprises) in order to fund their various projects. The way in which this new economic landscape is affecting local political arrangements is a heretofore little considered, yet highly consequential, development of the recent ‘migrant crisis’. This paper argues that emergence of migrant smuggling as a central economic pillar of Northern Mali has produced a more diversified and decentralized economic landscape, which in turn has led to a more diffused political environment that goes some way towards accounting for the protracted and fractionalized nature of the conflict. By exploring the effect of migration flows on conflict, as opposed to the other way around, this paper hopes provide an updated account of the political economic landscapes of conflict zones where migrant smuggling serves as a central pillar, as well as anticipate how the emerging 'age of migration' will impact some of the world's most vulnerable and unstable regions.